RESEARCH ON THE LIKELIHOOD RATIO OF REGISTERED UNIDENTIFIED SIGNALS OF SATELLITE ENVIRONMENTAL MONITORING OF ATMOSPHERE - K. Baev, Georgi (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Optical studies from the board of satellites are among the most informative. From space, in certain narrow spectral windows of the atmosphere environmental monitoring of the atmosphere is possible to be implemented. Objects of study are natural sources of environmental pollution and anthropogenic sources of pollution.